Smooth muscle angiotensin II type 1A receptor is required for abdominal aortic aneurysm formation induced by angiotensin II plus β-aminopropionitrile. (March 2023) - Okuno, Keisuke; Torimoto, Keiichi; Cicalese, Stephanie M.; Hashimoto, Tomoki; Sparks, Matthew A.; Rizzo, Victor; Eguchi, Satoru
Graphical abstract: Unlabelled Image